Screening and morphological observations of endophytic mold origin of pennywort (Centella asiatica (L.) Urban) as extracellular enzyme producer - Muhamad Aditya Hidayah; Retno Aliyatul Fikroh (JURNAL SAINS NATURAL, 2021)
Pennywort is a biological plant that is included in the medicinal plant species. The analysis was carried out to obtain information and to find out that endophytic molds from pennywort (Centella asiatica (L.) Urban) can produce extracellular enzymes (amylase, cellulase, pectinase, protease, glucanase, and laccase). Based on the analysis that has been carried out, several conclusions are obtained, endophytic fungi from pennywort with isolate codes MB 20, MM 1, MM 6, MM 8, and MM 16 capable of producing extracellular amylase enzymes, endophytic fungi from pennywort with isolate codes MM 1, MM 12, MM 16, MM 18, MM 19, MM 20 and MM 21 were able to produce extracellular cellulase enzymes, endophytic fungi from pennywort with isolate codes MB 1, MB 3, MB 4, MB 6, MM 1, MM 9, MM 11, MM 13, MM 14, MM16, MM 19, MM 20 and MM 21 were able to produce extracellular glucanase enzymes, endophytic mold isolates from pennywort were proven to be unable to produce extracellular enzymes laccase, pectinase, and protease, and endophytic molds from pennywort with isolate codes MB 1, MB 20, MM 14 and the MM 16 is capable of producing siderophores.Keywords: Centella asiatica (L.) Urban, extracellular enzymes, endophytic typite, isolatesABSTRAKSkrining pengamatan morfologi kapang endofit asal tanaman pegagan (Centella asiatica (L.) Urban) sebagai penghasil enzim ekstraselulerTanaman pegagan merupakan tanaman hayati yang termasuk dalam jenis tanaman obat. Analisis dilakukan untuk mendapatkan informasi dan mengetahui bahwa kapang endofit asal tanaman pegagan (Centella asiatica (L.) Urban) dapat menghasilkan enzim ekstraseluler (Amilase, selulase, pektinase, protease, glukanase, dan lakase). Berdasarkan analisis yang telah dilakukan di peroleh beberapa kesimpulan, diantanya. yaitu kapang endofit asal tanaman pegagan dengan kode isolat MB 20, MM 1, MM 6, MM 8 dan MM 16 mampu menghasilkan enzim amilase ekstraseluler, kapang endofit asal tanaman pegagan dengan kode isolat MM 1, MM 12, MM 16, MM 18, MM 19, MM 20 dan MM 21 mampu menghasilkan enzim selulase ekstraseluler, kapang endofit asal tanaman pegagan dengan kode isolat MB 1, MB 3, MB 4, MB 6, MM 1, MM 9, MM 11, MM 13, MM 14, MM16, MM 19, MM 20 dan MM 21 mampu menghasilkan enzim glukanase ekstraseluler, isolat kapang endofit asal tanaman pegagan terbukti tidak mampu menghasilkan enzim ekstraseluler lakase, pektinase dan protease, dan kapang endofit asal tanaman pegagan dengan kode isolat MB 1, MB 20, MM 14 dan MM 16 mampu menghasilkan siderofor.Kata Kunci: Centella asiatica (L.) Urban, enzim ekstraseluler, kapang endofit,  isolat